PDGF, NGF, and EGF as main contributors to tumorigenesis in high-risk retinoblastoma - Al-Ghazzawi, Karim; Wessolly, Michael; Dalbah, Sami; Ketteler, Petra; Kiefer, Tobias; Bechrakis, Nikolaos; Leyla, Jabbarli; Ting, Saskia; Biewald, Eva; Mairinger, Fabian D. (Frontiers in Oncology, 2023)
Retinoblastoma (RB) is the most primary cancer of the eye in children and an aggressive malignancy associated with excellent survival rates in high income countries however less favorable prognosis in third world countries. Early diagnosis can maximize the patient’s visual outcome as well as survival rate. Therapy should be conducted in highly specialized treatment centers. intravenous chemotherapy (IVC) forms the main pillar of therapy in the current century. Thermochemotherapy (TCT), intra-arterial chemotherapy (IAC) as well as radiation can be taken into consideration depending on extent and size of the tumor. Nonetheless, children and parents remain under constant stress revising doctors for medical treatment, fearing vision loss and even enucleation of the eye. Adequate molecular patient stratification to improve targeted therapy is still lacking. This retrospective study analyzed formalin fixed paraffin embedded specimens from a cohort of 23 RBs. Twelve of those samples showed undifferentiated (URB) histopathological risk feature, the other 11 differentiated (DRB) histopathological grading. RNA of all samples was isolated and analyzed via digital gene expression patterns. Whereas conductors of cell survival and DNA Repair were dominant in DRB samples compared to agents responsible for Cell-Cycle progression and apoptosis being overexpressed in URB samples. Our work reveals the importance of molecular mechanisms within the immune system subjected to histologic subtypes of RB, providing a more detailed background of their immunogenic potential. This is of great interest regarding therapeutic strategies including targeted immunotherapy in Retinoblastoma.